2016
DOI: 10.1371/journal.pntd.0004496
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Intestinal Protozoan Infections with Cryptosporidium, Giardia, Blastocystis and Dientamoeba among Schoolchildren in Tripoli, Lebanon

Abstract: BackgroundIntestinal protozoan infections are confirmed as major causes of diarrhea, particularly in children, and represent a significant, but often neglected, threat to public health. No recent data were available in Lebanon concerning the molecular epidemiology of protozoan infections in children, a vulnerable population at high risk of infection.Methodology and Principal FindingsIn order to improve our understanding of the epidemiology of intestinal pathogenic protozoa, a cross-sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
129
8
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(172 citation statements)
references
References 71 publications
(84 reference statements)
22
129
8
13
Order By: Relevance
“…22,40,41 However, Abdulsalam and others and Osman and others detected no significant difference in the rates of blastocystosis between drinking treated and untreated water, and suggested that the level of contamination of groundwater by Blastocystis was likely to be low. 2,15 In the present study, majority of the participants used bottled water (80.4%), and the remaining consumed tap water (19.6%), but no statistical difference was found in the infection rates between the two groups.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…22,40,41 However, Abdulsalam and others and Osman and others detected no significant difference in the rates of blastocystosis between drinking treated and untreated water, and suggested that the level of contamination of groundwater by Blastocystis was likely to be low. 2,15 In the present study, majority of the participants used bottled water (80.4%), and the remaining consumed tap water (19.6%), but no statistical difference was found in the infection rates between the two groups.…”
Section: Discussioncontrasting
confidence: 51%
“…Our finding was inconsistent with those of previous studies in which significant relation was detected between blastocystosis and gastrointestinal symptoms in symptomatic individuals. 1,2,15,37 In the present study, the most common Blastocystis STs were ST3, ST2, ST1, and ST4. Among these, only four STs (ST1, ST2, ST3, and ST4) are common throughout the world and their distribution also depends on geographic regions.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations